Regional policy and hydroelectric resources - Franco Romerio (Revue de Géographie Alpine)
This article brings to light the different models applied in the management of hydroelectric resources in the Swiss canton Ticino during the 20th century. Future prospects are broached in view of the opening of the electricity markets to competition. We equally analyse political projects, notably regarding matters of water cantonalisation, as well as the technico-economic factors which influence them. Conflicts, that have been particularly acute, are evoked, and socio-economic, energy and environmental issues detailed. The national and international context is pointed out. The study allows the identification of critical factors that must be considered in the definition of regional policies in relation to hydroelectric matters.